Perceptions of Multiple Perpetrator Rape in the Courtroom - Kelly C. Burke; Jonathan M. Golding; Jeffrey Neuschatz; Libbi Geoghagan (Behavioral Sciences, 2025)
Rape is typically committed as a one-on-one crime. However, a relatively high number of rapes (2–27%) involve a single victim and multiple perpetrators. These cases are often referred to as “gang” rapes but are also termed Multiple Perpetrator Rape (MPR). Despite these data, there is a scarce amount of legal decision-making research on this issue. This study investigated legal decision making in an acquaintance rape case involving multiple perpetrators. This study was a 2(Defendant Number: one vs. three) × 2(Victim Intoxication: intoxicated vs. sober) × 2(Participant Gender: women vs. men) between-participants design. Online community members (N = 171) were randomly assigned to read a trial summary involving one of four conditions. The primary results showed that, when the case involved multiple (vs. one) perpetrators, mock jurors were more likely to vote guilty, perceived the victim to be more helpless, and reported less sympathy for the defendant and lower defendant credibility. Cognitive networks showed that jurors in the MPR condition emphasized the number of perpetrators as a primary reason for voting guilty. Finally, there was evidence of a serial indirect effect involving victim helplessness and defendant blame that explained the relation between the number of defendants and verdicts, as well as parallel indirect effects of defendant credibility, sympathy, and anger, and victim helplessness on verdicts. Implications for prosecuting MPR cases are discussed.